2022
DOI: 10.1186/s42358-022-00240-9
|View full text |Cite
|
Sign up to set email alerts
|

Official Position of the Brazilian Association of Bone Assessment and Metabolism (ABRASSO) on the evaluation of body composition by densitometry—part II (clinical aspects): interpretation, reporting, and special situations

Abstract: Objective To present an updated and evidence-based guideline for the use of dual-energy x-ray absorptiometry (DXA) to assess body composition in clinical practice. Materials and methods This Official Position was developed by the Scientific Committee of the Brazilian Association of Bone Assessment and Metabolism (Associação Brasileira de Avaliação Óssea e Osteometabolismo, ABRASSO) and experts in the field who were invited to contribute to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…The authors stated that the data on ALM remain inconclusive because the studies reported the results inconsistently across upper or lower skeletal regions. The ALMI used in the present study, which is an adjusted ratio of ALM to height, is a validated criterion for assessing lean mass that has shown a consistent correlation with muscle mass throughout life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that the data on ALM remain inconclusive because the studies reported the results inconsistently across upper or lower skeletal regions. The ALMI used in the present study, which is an adjusted ratio of ALM to height, is a validated criterion for assessing lean mass that has shown a consistent correlation with muscle mass throughout life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALMI was obtained as the ratio of ALM to height 2 . An FMI of 6–9 kg/m 2 and an ALMI ≥ 5.45 kg/m 2 were considered normal body fat [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…This region, also called android region, comprises the area located between the ribs and pelvis, with demarcation greater than 20% of the distance between the iliac crest and the neck and a lower demarcation at the top of the pelvis. 14 …”
Section: Methodsmentioning
confidence: 99%
“…The DXA execution method is safe, using low-intensity X-rays, which allows to measure bone mass, LM and FM individually. 14,15 Some studies show a significant increase in LM throughout the treatment, at the end of the follow-up period, and in comparison with the control group, with the effect being more evident in boys and during the first year of treatment. The main determinant of reported LM gain is length, as growth recovery was accompanied by an increase in LM, especially during the first year of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation